(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
A large amount of consumer oil is currently imported into the country from abroad, which in turn leads to high import prices. To provide the population with cheap and high-quality oil products, it is necessary to increase the cultivation of oilseeds in the country, to improve the technology for the production of oils and their introduction into production.